THE IMPLEMENTATION EFFECTIVENESS OF HOSPITAL RESPONSIBILITY TOWARDS HEALTHCARE WORKERS IN COVID19 ERA AT HOSPITAL X SUKABUMI - Susilo Kurniawan Yeo; Andry Andry; Ratna Indrawati (Jurnal Ilmiah Teunuleh, 2021)
Since the Coronavirus Disease 2019 (COVID-19) pandemic occurred in Indonesia, the health workers have become both an important entity in fighting COVID-19 and has high risk of being exposed to COVID-19. They required high protection for their safety. This work aimed to describe the applicable laws and regulations in Indonesia regarding the responsibility of Hospitals to Healthcare Workers in the COVID-19 Era and to test the effectiveness of regulation implementation. A phenomenological study approach was applied in this study. The thematic analysis was conducted to obtain the main theme of this study. The results revealed six laws and regulations were related to the hospitals’ responsibility toward healthcare workers which were Law number 36 of 2009 concerning Health, Law number 44 of 2009 concerning Hospitals, Government Regulation Number 88 of 2019 concerning Occupational Health, Minister of Health Regulation number 66 of 2016 concerning Hospital Occupational Health and Safety, Minister of Health Decree number 413 of 2020 concerning Guidelines for the Prevention and Control of Coronavirus Disease 2019, and Decree Number 392 of 2020 concerning Incentives and Death Compensation for Healthcare Workers.